2020
DOI: 10.21203/rs.3.rs-28659/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong negative covariation between toxoplasmosis and CoVID-19 at a global scale: a spurious indirect effect?

Abstract: Coronaviruses may exert severely negative effects on the mortality and morbidity of birds and mammals including humans and domestic animals. Most recently CoVID-19 has infected over 2,360,000 humans and killed more than 165,000. Susceptibility to this disease appears to differ markedly across different societies but the factors underlying this variability are not known. Given that toxoplasmosis exerts both direct and immune-mediated antiviral effects, we hypothesize a negative covariation between toxoplasmosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Other obtained results showed that, excluding countries where peak of infections occurred very early and its duration was short, the higher GDP per capita, the earlier peak occurs and the first epidemic wave is shorter. This result, in turn, is similar to another very recent paper, which reported that the date of first CoVID-19 cases co-varies positively with GDP across countries, most probably due to their more intensive participation of the global tourism and traffic industries (Jankowiak et al 2020). The other example showed that the higher population density the lower the percentage of population infected during first wave of infections.…”
Section: Discussionsupporting
confidence: 90%
“…Other obtained results showed that, excluding countries where peak of infections occurred very early and its duration was short, the higher GDP per capita, the earlier peak occurs and the first epidemic wave is shorter. This result, in turn, is similar to another very recent paper, which reported that the date of first CoVID-19 cases co-varies positively with GDP across countries, most probably due to their more intensive participation of the global tourism and traffic industries (Jankowiak et al 2020). The other example showed that the higher population density the lower the percentage of population infected during first wave of infections.…”
Section: Discussionsupporting
confidence: 90%